Determinants of FDI in Czech manufacturing industries between 2000-2006 - Eva Ryšavá; Elisa Galeotti (Charles University in Prague, Institute of Economic Studies (IES), 2009)
The Czech Republic has been a successful recipient of foreign direct investment over recent years. Therefore, it is important to understand the decisions made by foreign investors where to place their investments and how to decide about their location between alternative industries. The aim of this paper is to find and estimate an econometric model describing the determinants of foreign direct investment (FDI) in manufacturing industry of the CR between 2000-2006. Our model includes several basic economic variables (for example labor, physical capital, R&D, profits per labor. Together with simple techniques of estimation (OLS, fixed effects) we used generalized method of moments (GMM). As an additional technique we used also least trimmed squares estimator (LTS) as a diagnostic tool for the heterogeneous pattern of data.
Keywords: C01; C23; C51; C82; F21; F40; 330; foreign direct investment; Czech Republic; manufacturing industry; panel data; GMM; Direktinvestition; Verarbeitendes Gewerbe; Schätzung; Tschechische Republik